Solvay : history of a multinational family firm - Bertrams, Kenneth, 1977-; Coupain, Nicolas, 1978-; Homburg, Ernst, 1952-; Kurgan-Van Hentenryk, Ginette, 1938-; Mioche, Philippe, 1953- (Cambridge ; New York : Cambridge University Press, 2013)
"Ernest Solvay, philanthropist and organizer of the world-famous Solvay conferences on physics, discovered a profitable way of making soda ash in 1861. Together with a handful of associates, he laid the foundations of the Solvay company, which successfully branched out into other chemicals, plastics and pharmaceuticals. Since its emergence in 1863, Solvay has maintained world leadership in the production of soda ash. This is the first scholarly book on the history of the Solvay company, which was one of the earliest chemical multinationals and today is among the world's twenty largest chemical companies. It is also one of the largest companies in the field to preserve its family character. The authors analyze the company's 150-year history (1863-2013) from economic, political and social perspectives, showing the enormous impact geopolitical events had on the company and the recent consequences of global competition"--
Part I. The Pioneering Years (1863-1914): The Quest for a Leadership and the First Stages of the Internationalization: 1. First steps: when vision and reality meet; 2. A multinational pioneer; 3. Reaching a dominant position; 4. Labor organization, social policy, and societal vision; 5. The consolidation of power; 6. Conclusion of Part I; Part II. The Years of Crisis (1914-50): The Making and Unmaking of International Alliances: 7. The multiple fronts of World War One; 8. From ashes, 1918-22; 9. The making of international alliances; 10. Family and finance through the crisis; 11. The electrolytic industry; 12. Facing war again; 13. Solvay's second postwar period; 14. Conclusion of Part II; Part III. The Era of Diversification and Globalization (1950-2012): 15. Growth through diversification: the successful entry into plastics and peroxides; 16. Enlarging scale and scope: backward and forward integration in the 1960s and 1970s; 17. Solvay goes public: financial and organizational limits of a family firm; 18. The long and winding road to Deer Park: Solvay's return to the United States; 19. From bulk to brains: Solvay's entry into pharmacy and the life sciences; 20. Solvay in the age of globalization; 21. Towards sustainable product-leadership; 22. Chemical and plastics of the future: major turning points at the start of a new century; 23. Conclusion of Part III.
Includes bibliographical references (p. 577-599) and index.
Keywords: Solvay, Ernest, -- 1838-1922.; Solvay Chemicals -- History; Business & economics -- Economic history; Chemical industry -- History -- Belgium; International business enterprises -- Belgium; Philanthropists -- Belgium